Bone-like coatings deposition by using of modern pulsed ion-plasma technology - Zykova, A.V.; Dudin, S.V.; Polozhiy, K.I. (Вопросы атомной науки и техники, 2003)
The technology of synthesis of multilayer coatings on the basis of alumina oxide and structures, like tricalcium phosphate and hydroxylapatite, was suggested by Reactive Ion-Beam Synthesis (RIBS) method in a same vacuum cycle. The substance of the method consists in a physical sputtering of target of compound composition on the specimens with its simultaneous bombardment by intensive ion beams of chemically active gases. The concurrent using of pulsed ion-plasma technology offer the ability to beneficially modify a wide array of surface properties at low temperature; to increase adhesion, density, deposition rate and quality of oxide coatings, to deposit complex multilayer dielectric coatings with ultra disperse structure. The analysis of results obtained in the work, allows to make a conclusion about the advantages of combining of pulsed ion-plasma technology with RIBS method using for the purpose of strong attachment of metal prosthesis in bone tissue and the activation of osseogenesis and osseointegration processes.